Reexamining academic reading skills of unemployed graduates through the English Language E-Training (ELET) Module/ Noriah Ismail, Soo Kum Yoke and Normah Ismail - Ismail, Noriah; Soo, Kum Yoke; Ismail, Normah (UiTM Cawangan Johor, 2018)
The study investigates the effects of the English Language E-Training (ELET) Reading Module in Enhancing the academic reading skills among 30 BBA(Bachelor of Business Administration) unemployed graduates. The research consists of a pretest, the application of the module and the post-test. A survey questionnaire was also deployed in order to find out the participants’ learning styles and readiness towards the ESP e-training program as well as their perception towards the online module. The findings revealed that the ELET Reading module is able to significantly enhance the participants’ academic reading skills. Furthermore, the survey indicates the participants’ readiness and positive reception towards ELET reading module.